Genotypic and functional comparisons of Epstein-barr virus latent membrane protein-1 from different stages of nasopharyngeal carcinoma - Tan, Eng Lai; Sam, Choon Kook (Penerbit Universiti Sains Malaysia, 2004)
Epstein-Barr virus (EBV) latent membrane protein 1 (LMP1), has all the typical characteristics of an oncogene and extensive studies have shown beyond doubt its abilities in cellular transformation giving rise to malignant phenotypes. NPC carcinogenesis, as typical as any other solid tumours, is a multi-step process. One of the most important EBV latent genes expressed in NPC is the viral oncogene, latent membrane protein-1 (LMP1).